American Gamelan and the Ethnomusicological Imagination - Clendinning, Elizabeth A., 1987- (Book collections on Project MUSE., 2020)
"Gamelan and American academic institutions have maintained their close association for more than sixty years. Elizabeth A. Clendinning illuminates what it means to devote one's life to world music ensemble education by examining the career and community surrounding the Balinese-American performer and teacher I Made Lasmawan. Weaving together stories of Indonesian and American practitioners, colleagues, and friends, Clendinning shows the impact of academic world music ensembles on the local and transnational communities devoted to education and the performing arts. While arguing for the importance of such ensembles, Clendinning also spotlights how performers and educators use them to create stable and rewarding artistic communities. Cross-cultural ensemble education emerges as a worthy goal for students and teachers alike, particularly at a time when people around the world express more enthusiasm about raising walls to keep others out rather than building bridges to invite them in"--